Effect of repeated sprint exercises on cardiac autonomic recovery in adolescent and adult males: an experimental trial - Paulo Francisco de Almeida-Neto; Júlio Alves; Gilmara Gomes de Assis; Roberto Felipe Câmara Rocha; Fernanda Cristina Silva de Oliveira; Iago Medeiros da Silva; Ayrton de Bruno Morais Ferreira; Matheus de Lima Rocha; Felipe J. Aidar; Paulo Moreira Silva Dantas; Breno Guilherme de Araújo Tinôco Cabral (Human Movement)
Purpose Repeated sprint exercises (RSEs) are widely used to improve physical fitness; however, their specific effects on cardiac autonomic recovery (CAR) in individuals of different ages and biological maturation (BM) stages still lack investigation. Our objective was to analyse the effect of RSE on CAR, assessed by the heart rate (HR) recovery index and the time and frequency domains of heart rate variability (HRV) in male adolescents and adults.